Electrostatic‐Induced Crystal‐Rearrangement of Porous Organic Cage Membrane for CO2 Capture. (15th June 2022) - Qu, Kai; Xu, Jipeng; Dai, Liheng; Wang, Yixing; Cao, Hongyan; Zhang, Dezhu; Wu, Yulin; Xu, Weiyi; Huang, Kang; Lian, Cheng; Guo, Xuhong; Jin, Wanqin; et al.
Abstract: Porous Organic Cages (POCs) with tunable tailoring chemistry properties and polymer‐like processing conditions are of great potential for molecular selective membranes, but it remains challenging in the assembly of high crystalline POCs with regular nanochannels for effective molecular sieving. Here we report an electrostatic‐induced crystal‐rearrangement strategy for the design of a POC membrane with heterostructure. Due to electrostatic attraction, ionic liquid molecules induced cage molecules to rearrange into a sub‐10 nm uniform and defect‐free crystal layer, which displayed competitive CO2 separation performance. The optimized hetero‐structured membrane exhibited an attractive CO2 /N2 separation selectivity of over 130, which was superior to the state‐of‐the‐art membranes, accompanied with excellent long‐term and thermal shock stability. This strategy provides a new inspiration for the preparation of crystal‐rearranged membranes with regular channels for gas molecule sieving. Abstract : Competitive CO2 capture in a porous organic cage membrane can be assisted by ionic liquid molecules (e.g., BMIMBF4 ). Ionic liquid molecules electrostatically induce the crystal‐rearrangement of cage molecules to construct regular nanochannels as well as aiding in situ nanochannel regulation.